Avaliação de subprodutos do abate de animais terrestres e de resíduos do processamento de peixes como fonte de proteína em rações para o camarão branco do pacífico, Litopenaeus vannamei (BOONE, 1931) - Santos, Pedro Henrique Gomes dos (2013)
The dietary effects of land and aquatic animal by-products on the growth performance of the white shrimp Litopenaeus vannamei are little known. This study evaluated the growth performance and feeding responses of juvenile shrimp L. vannamei when fed diets which partially or completely replaced a salmon byproduct meal for rendered animal byproducts obtained from the slaughtering of land animals and from fish processing waste. The work was divided into two phases, one consisting of rearing 2.03 ± 0.21 g shrimp for 72 days in 500 l tanks, under clear-water with continuous water recirculation and filtration. In the second phase, two-by-two comparisons were carried out with each individual ingredient in a double-choice aquarium using 7.12 ± 0.65 g shrimp. In the growth study, diets consisted of a control diet S14 with 14.37% of a salmon byproduct meal, while others contained animal proteins in partial or complete replacement of this ingredient: diet PL7+S10 with 7.00% spray-dried swine plasma meal, diet SG7+S9 with 7.00% spray-dried blood meal, diet Ca13+S6 with 12.95% meat and bone meal 40% crude protein (CP), diet Pn14+S4 with 14.39% hydrolyzed feather meal, diet CB18+S2 with 17.72% meat and bone meal 45% CP, diet Til15 with 15.12% farmed-tilapia processing waste meal, diet PV15 with 16.24% poultry byproduct with feather meal, diet V16 with 16.24% poultry byproduct meal and diet Px19 with 18.67% fisheries by-catch and processing waste meal. For the attractability assays, animal protein ingredients were added at a 3.0% dietary inclusion in a plant-based diet. At harvest, shrimp displayed statistically significant differences for all growth parameters evaluated. With the exception of diet S9+SG7, all other diets led to a reduction in the final body weight of L. vannamei compared to the control diet (11.05 ± 0.18 g). In comparison to diet S14, there was also a significant loss in the gain of yield (diet PV15, 288 ± 30 vs. 555 ± 59 g/m2), weekly growth (diets PV15, Til15 and CB18+S2, 0.55 ± 0.02, 0.60 ± 0.05, 0.67 ± 0.04 vs. 0.87 ± 0.07 g, respectively), feed intake (diet PV15, 8.9 ± 0.42 vs. 13.5 ± 0.02 g/shrimp) and feed conversion ratio (diet PV15, 2.24 ± 0.18 vs. 1.74 ± 0.08). The percentage of positive choices and (or) rejection of feed intake was poorer for all animal ingredients than the salmon byproduct meal, except for the meat and bone meal 45% CP, the hydrolyzed feather meal and the poultry by-product meal. In conclusion, in diets for juvenile shrimp L. vannamei, the spray-dried blood meal and the poultry by-product meal, were the most recommended animal ingredients for partial and total replacement of salmon byproduct meal,respectively, within the maximum levels of dietary inclusion adopted.